A simplified flange–lip model for distortional buckling of cold-formed steel channel-sections with stiffened web. (February 2018) - Huang, Xu-hao; Yang, Jian; Liu, Qing-feng; Zhu, Jue; Bai, Li; Wang, Fei-liang; Wang, Jian-hua
Highlights: A simplified flange–lip model is proposed to analyze the distortional buckling of CFS thin walled -section. The equivalent orthotropic plate model is employed to analyze the local buckling of thin walled sections. The simplified model can be adopted in the direct strength method (DSM). Abstract: This paper presents a simplified analytical model for determining the critical stress of distortional buckling of lipped channel-sections with stiffened web made from cold-form steel (CFS). Lipped channel-section with stiffened web have been shown to have a distinct advantage in resisting local buckling and are associated with the higher distortional buckling stress, when compared to the channel-section without stiffeners. It is widely used as a substitution for standard channel-section in cold form steel construction applications. In the current work, CFS channel-sections with stiffened web are investigated based on the flange–lip model. In order to determine the stiffness of rotational springs representing the restraining effect of the web to the flange–lip system, the web with different type of stiffeners is modeled as an orthopedic plate. Using the total potential energy principle, the formula for calculating the local buckling stress of the stiffened web considering loading scenarios including a pure compression and a pure bending moment are derived. The stiffness of rotational spring can be obtained. Finally, the prediction of distortional buckling critical stress of lipped channel-section with different type of stiffened webs is carried out, which is shown to be in good agreement with those calculated by the finite strip method (FSM). Graphical abstract: